Structural Modeling of the Enhancement of the Electronic Professional Learning Environment for Managers (Case Study: Bandar Abbas Oil Refinery) - Moayeri , MohammadReza; Nami, Kolsum; Rahmani , Moammadnoor; Abedini, Mahnoosh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The present study aimed to model the structural enhancement of the electronic professional learning environment for managers at the Bandar Abbas Oil Refinery.Method: This descriptive correlational study was conducted on 166 managers, deputies, and employees of the Bandar Abbas Oil Refinery who were selected using stratified random sampling. In this research, a researcher-made questionnaire was used, based on the model by Nami et al. (2022), which was validated in terms of reliability by Cronbach's alpha (above 0.70 for all indicators) and in terms of validity by experts. Data analysis was performed using LISREL software, employing Kolmogorov-Smirnov tests and structural equation modeling with confirmatory factor analysis.Findings: The results indicate that with significant numbers, it can be said: The dimensions of education, organization, environment, management, economics, communication, individual, technology, and standardization of education have a significant and positive relationship with the enhancement of the electronic professional learning environment for managers in the Bandar Abbas Oil Refinery (P < 0.001).Conclusion: Consequently, electronic professional learning environments have unique capacities for designing and implementing learning for managers, which enriches the learning experiences of managers.